Role of artificial intelligence chatbot marketing in enhancing customer satisfaction and loyalty in digital shopping experiences - Alsadoun, Abdullah Ali; Alnasser, Asem Nasser (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to explore the impact of AI chatbot marketing on customer satisfaction and loyalty within the context of online shopping in Saudi Arabia. It seeks to understand how the usability and responsiveness of AI chatbots influence customer perceptions and behaviors, ultimately contributing to enhanced satisfaction and loyalty. A cross-sectional research design was employed, utilizing a structured questionnaire to collect data from 271 customers with prior experience in online shopping. Convenience sampling was used to gather responses, and the questionnaire included dimensions related to the usability and responsiveness of AI chatbots. Structural equation modeling (SEM) was applied to analyze the data and assess the relationships between AI chatbot marketing, customer satisfaction, and customer loyalty. The results reveal that AI chatbot marketing significantly enhances customer satisfaction, which in turn positively influences customer loyalty. Additionally, customer satisfaction was found to mediate the relationship between AI chatbot marketing and customer loyalty. These findings highlight the critical role of AI chatbots in shaping customer experiences and fostering long-term loyalty. The study concludes that AI chatbot marketing is a powerful tool for improving customer satisfaction and loyalty in the online shopping environment. By investing in advanced AI technologies and optimizing chatbot functionalities, businesses can create more engaging and satisfying customer interactions. The findings suggest that businesses should prioritize the development and implementation of AI chatbots to enhance customer experiences. By focusing on usability and responsiveness, companies can drive higher levels of satisfaction and loyalty, thereby gaining a sustainable competitive advantage in the digital marketplace. These insights are particularly relevant for online retailers in Saudi Arabia and other regions aiming to capitalize on the growing trend of AI-driven customer engagement.